2018
DOI: 10.1002/app.46420
|View full text |Cite
|
Sign up to set email alerts
|

Design and study of the potential of crosslinked cationic polymers as drug delivery systems for dermal application

Abstract: Crosslinked carriers based on cationic monomer [2-(acryloyloxy)ethyl]trimethylammonium chloride or 2-(dimethylamino)ethyl methacrylate were developed and investigated as new platform for ibuprofen transdermal delivery. Series of networks of varied composition and structure were synthesized and characterized by FTIR spectroscopy and following swelling kinetics in different solvents. Dermal safety tests to examine the skin irritation and sensitization potential of the network films were performed in vivo. Chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The researchers thought that cationic polymers should never be considered as an inert, biocompatible component of biotechnological applications aimed to interact with living systems. In 2018, Bistra et al [144] synthesized reticular PDAC on a 1 mm glass sheet by adding crosslinking agents and used the reticular PDAC as a crosslinking carrier for ibuprofen administration in vivo for a skin safety test. It was found that ibuprofen was released from the drug delivery system in a phosphate buffer solution at 37~38 • C, demonstrating the feasibility of cationic cross-linked polymers as effective carriers for the sustained release of ibuprofen.…”
Section: Medicinementioning
confidence: 99%
“…The researchers thought that cationic polymers should never be considered as an inert, biocompatible component of biotechnological applications aimed to interact with living systems. In 2018, Bistra et al [144] synthesized reticular PDAC on a 1 mm glass sheet by adding crosslinking agents and used the reticular PDAC as a crosslinking carrier for ibuprofen administration in vivo for a skin safety test. It was found that ibuprofen was released from the drug delivery system in a phosphate buffer solution at 37~38 • C, demonstrating the feasibility of cationic cross-linked polymers as effective carriers for the sustained release of ibuprofen.…”
Section: Medicinementioning
confidence: 99%
“…Hydrogels are advantageous delivery systems for hydrophilic drugs because dissolved drugs could be included in the swollen cross-linked polymer matrix [ 29 , 30 , 31 ]. A variety of network structures could be used for the development of hydrogels suitable for dermal drug delivery applications, including copolymer architectures [ 38 , 39 , 40 ] and interpenetrating (IPN) and semi-interpenetrating networks [ 41 , 42 , 43 ]. A high swelling capacity in water and in body liquids of the networks, which reduces the irritancy of the carrier, is of prime importance, along with the general requirements for biocompatibility and non-toxicity.…”
Section: Introductionmentioning
confidence: 99%